Tombak Kawauka (Menangis) Warisan Leluhur Alm. Kakek Rato Bili Dagawoli Dikampung Adat Leluhur Bumalere - David Loba (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Bumalere village is located in the Loura region in the upper mountains of Karuni spring and at the bottom of Bumalere village there is a spring called Likku spring. Bumalere village is overgrown with trees, thorn bushes, steep rocks and large rice fields in the foothills between the Likku and Aba rivers. To reach this village you have to pass through paths and rocks with heights and steep bottom ravines that require energy and it was customary at that time to make houses for each tribe / Kabihu including the Bumalere tribe to make houses on steep mountains in order to avoid enemies who could attack and rob, rob, burn, rape, take inheritance or the contents of traditional houses or anything that could be brought down by the enemy and even bring people who were made their servants / slaves and traded back.